Insect Succession and Dynamics on Decomposing Piglets (Sus domesticus Erxleben) Carasses at Umudike, Southeast Nigeria - , Ehisianya, C. N.; , Ozum, E. K.; , Okore, O. O. (Archives of Current Research International, 2024)
Aim: To determine the identity and distribution of insects colonizing ground-placed and hung decomposing domestic piglets (Sus domesticus) carcasses. Place and Duration: Michael Okpara University of Agriculture, Umudike, Abia State, Nigeria. Study carried out in two seasons: July to September, 2019 (wet), and January to March, 2020 (dry). Methodology: Four healthy piglets with average weight of 3.73 kg were sacrificed for the trial by dislocating their cervical vertebrate (to mimic natural death), and put in cages. Two were placed on the ground, whereas the other two were hung on a tree. Data on arthropod populations, temperature, weights and decomposition stages and rates of carcasses were collected. Statistical tests were performed to evaluate insect species distribution and their relationships with the carcasses. Results: Irrespective of placement, more insects were counted during the dry (655.20) than wet (529.96) seasons but not statistically different. The distribution of insects’ taxa showed Musca spp. (37.09 %), Chrysomya spp. (12.97 %), Pheidole spp. (12.09), Componotus spp. (9.69 %), Monomorium spp. (6.04 %) in seventeen genera, ten families in four orders. The relationship between insects’ abundance and mean weight were significantly (P = 0.05) negative (-0.53) and (-0.96) in the ground-place carcasses in the wet and dry seasons, respectively. Conclusion: Results show that Musca spp. was the predominant species and Dysdercus spp. was the least throughout the decomposition period. Higher number of insects were counted from the carcasses in the dry than wet seasons. Insects’ abundance increases as the carcasses’ weights decreased.